Phytochemical Content, Antioxidant, Alpha-Glucosidase Inhibitory and Antibacterial Activities of Spineless Cactus Pear Cultivars - Mologadi B. Mabotja; Sonja L. Venter; Christian P. Du Plooy; Tukayi Kudanga; Stephen O. Amoo (Plants, 2021)
Variation in cultivars can influence plant biological activities. This study aimed to identify superior cultivars while determining the variability in the phytochemical content, antioxidant, alpha-glucosidase inhibitory and antibacterial activities of cladode extracts from selected spineless Burbank cactus pear (Opuntia ficus-indica and Opuntia robusta) cultivars. Total phenolic and flavonoid contents were determined using the Folin-Ciocalteu and aluminum chloride spectrophotometric methods, respectively. Antioxidant activity was investigated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging and β-carotene linoleic acid assays. Alpha-glucosidase inhibition was determined using a spectrophotometric method and antibacterial activity using a non-polar (petroleum ether) and polar (50% methanol) extracts against two Gram-positive and two Gram-negative bacteria. Significant variation in phytochemical content, antioxidant, antidiabetic and antibacterial activities was observed amongst the cultivars. Alpha-glucosidase inhibitory activity varied widely with IC50 values ranging from 0.06 to 1.85 mg/mL. Radical scavenging activity of Polypoly cultivar was about seven fold higher than that recorded in other cultivars with low activity. Turpin and Berg x Mexican cultivars had the highest total phenolic and flavonoid contents, whilst the non-polar extract of Turpin also exhibited higher antibacterial activity against Bacillus subtilis and Escherichia coli. Sicilian Indian Fig was amongst the cultivars with a higher antioxidant activity, whilst also showing a strong inhibition against B. subtilis and E. coli. Polypoly cultivar demonstrated strong antioxidant and antidiabetic activities while its polar extract showed the highest total antibacterial activity against B. subtilis. The cultivar Malta was superior in terms of its antibacterial potency and efficacy against B. subtilis, Staphylococcus aureus and E. coli. The potential of using spineless cactus pear cladodes as a functional food with antioxidant, antidiabetic and antibacterial properties against pathogenic food spoilage bacteria in place of synthetic compounds was established. The significance of cultivar selection to increase this potential was highlighted.